Różewicz reconstructed? - Pietrych, Krystyna (Porównania, 2023)
The article is a review of the book Różewicz. Rekonstrukcja. I [Różewicz. Reconstruction. I] by Magdalena Grochowska. It is the first part of her wide-ranging biographical work on Różewicz’s biography, which was published in the year of Różewicz's 100th birthday anniversary. The review presents the compositional idea of ​​the biography, based on a chronological order (from his birth to about 1957). This order is treated freely by Grochowska, because it is often abandoned in favor of thematic and problematic approaches (e.g. the issue of Różewicz’s Jewish origin, his relationships with mother and wife, his participation in Armia Krajowa [Home Army] battles during the 2WW and its influence on his later dramas). Critical consideration was given to the strategy used by the author of the book – an overly simple combination of plan and creativity through the use of literary works as a direct commentary on the poet's existence. Attention was also paid to the undoubted advantages of the publication – the presentation of the results of work in archives, as well as Magdalena Grochowska's excellent reporting skills.